2009
DOI: 10.1186/1471-2105-10-11
|View full text |Cite
|
Sign up to set email alerts
|

Filtering for increased power for microarray data analysis

Abstract: Background: Due to the large number of hypothesis tests performed during the process of routine analysis of microarray data, a multiple testing adjustment is certainly warranted. However, when the number of tests is very large and the proportion of differentially expressed genes is relatively low, the use of a multiple testing adjustment can result in very low power to detect those genes which are truly differentially expressed. Filtering allows for a reduction in the number of tests and a corresponding increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
231
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(232 citation statements)
references
References 11 publications
0
231
0
1
Order By: Relevance
“…Integrated peak height intensity was tabulated for 700 negative ion mass features (Dataset S1) and 1,164 positive ion features (Dataset S2). Data filtering removed 25% of the negative features and 40% of the positive features before analysis (37). Principal component analysis (PCA) showed that maximum variation in global metabolite pools was between individual ears independent of kernel genotype (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Integrated peak height intensity was tabulated for 700 negative ion mass features (Dataset S1) and 1,164 positive ion features (Dataset S2). Data filtering removed 25% of the negative features and 40% of the positive features before analysis (37). Principal component analysis (PCA) showed that maximum variation in global metabolite pools was between individual ears independent of kernel genotype (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Sequences were also assigned to phylotypes using the phylotype command in Mothur. A multivariate data analysis of the OTUs was performed using METAGENassist (Arndt et al, 2012), followed by normalization based on interquantile range (IQR) (Hackstadt and Hess, 2009) and log 2 -transformation. IQR normalization allows one to increase statistical power by removing sequences that do not fall within the middle 50% of observations and thus reducing the number of statistical tests one has to perform.…”
Section: Methodsmentioning
confidence: 99%
“…In the microarray literature, several authors have suggested filtering to reduce the impact that multiple testing adjustment has on detection power (7)(8)(9)(10)(11)(12). Conceptually similar screening approaches have also been proposed for variable selection in high-dimensional regression models (13,14).…”
mentioning
confidence: 99%